Pengenalan Perspektif Sistem Ekonomi Islam Pada Ikatan Keluarga XIII Koto Kampar Sadayuong - Assyifa, Zubaidah; Mairiza, Diany; Rahmawati, Rahmawati; Irmawanti, Irmawanti; Delia, Dwi Anisa (Journal of Community Sustainability, 2025)
This community service was conducted in Kampar Regency, Riau Province. The objects were members of the XIII Koto Kampar Sadayuong Bangkinang City Family Association. This community service aims to socialize the Perspective of the Islamic Economic System. The results of this community service indicate that: 1) The success of the target number of training participants. 2) Achievement of activity objectives. 3) Achievement of planned material targets. 4) The ability of participants in mastering the material. Overall, this community service activity can be said to be successful. This success, in addition to being measured from the four components above, can also be seen from the satisfaction of participants after participating in the activity because the community service provides the opportunity to ask as many questions as possible and when the community service provides questions, they can be answered by students, especially for students who can answer, they are given prizes. The benefits obtained by participants are knowledge and understanding of the Islamic economic system perspective.